A review of current induction strategies and emerging prognostic factors in the management of children and adolescents with acute lymphoblastic leukemia. Issue 7 (2nd July 2020) - Capria, Saveria; Molica, Matteo; Mohamed, Sara; Bianchi, Simona; Moleti, Maria Luisa; Trisolini, Silvia Maria; Chiaretti, Sabina; Testi, Anna Maria
ABSTRACT: Introduction: Acute lymphoblastic leukemia is the most frequent hematologic malignancy in children. Almost 95% of children potentially achieve a complete remission after the induction treatment, but over the last years, new insights in the genomic disease profile and in minimal residual disease detection techniques have led to an improvement in the prognostic stratification, identifying selected patients' subgroups with peculiar therapeutic needs. Areas covered: According to a comprehensive search of peer-review literature performed in Pubmed, in this review we summarize the recent evidences on the induction treatment strategies comprised in the children acute lymphoblastic leukemia scenario, focusing on the role of key drugs such as corticosteroids and asparaginase and discussing the crucial significance of the genomic characterization at baseline which may drive the proper induction treatment choice. Expert opinion: Current induction strategies already produce durable remissions in a significant proportion of standard-risk children with acute lymphoblastic leukemia. A broader knowledge of the biologic features related to acute lymphoblastic leukemia subtypes with worse prognosis, and an optimization of targeted drugs now available, might lead to the achievement of long-term molecular remissions in this setting.